Long-term rye monoculture on chernozem: stable yields with changing soil organic matter - Kokhan, Andriy; Tsyliuryk, Oleksandr; Len, Oleksandr; Shevchenko, Mykhailo; Shevchenko, Serhii; Izhboldin, Oleksandr; Samoilenko, Olena; Yevtushenko, Halyna; Olepir, Roman (Ecological Questions, 2025)
Long-term field experiments are essential for understanding how monocultures reshape soils under climate change. We hypothesised that the buffering capacity of Ukrainian chernozem sustains low but persistent winter rye yields without external inputs, while gradually altering the quality of soil organic matter and the base-cation status. We tested this in a long dataset from Poltava (Ukraine): a 0.4-ha plot established in 1884 and managed uniformly (annual disking and ploughing to 22–25 cm, mid-September sowing, no fertilisers, herbicides or pesticides; varieties renewed). Hydrometeorological records, archived yields (1885–2024) and repeated soil surveys (1964–2024) were analysed; elemental composition was determined by ICP-MS; humus fractions by standard alkaline extraction; statistics in Statistica 12. Mean grain yield was 1.19 t ha⁻¹ (straw 2.80 t ha⁻¹) with wide interannual variability (0.15–2.38 t ha⁻¹) but no significant long-term trend despite regional warming and modest precipitation decline. Topsoil humus (0–20 cm) decreased from 2.8% mid-century to 2.3% in 2024, and the humic: fulvic carbon ratio fell from 1.15 to 0.89, indicating a shift toward more mobile, less polymerised fractions. Soil reaction remained acid to slightly acid (pH(salt) 4.7–5.5) with hydrolytic acidity 2.4–3.8 meq 100 g⁻¹; available N, P and K fluctuated within stable ranges, but Ca and Mg declined. Weed communities changed markedly; pest pressure intermittently exceeded economic thresholds yet appeared buffered by natural antagonists. Continuous winter rye on chernozem maintains modest, persistent yields without fertiliser inputs, while organic matter quantity declines moderately and quality becomes more fulvic; concurrent base-cation depletion flags a risk to structural and ecological stability. The 140-year record provides a rare baseline for calibrating models and designing rotation, liming, and nutrient-return strategies for climate-resilient agro-ecosystems in Eastern Europe.